2021
DOI: 10.1002/cb.1966
|View full text |Cite
|
Sign up to set email alerts
|

Physically processing imperfect produce: The impact of prototypicality

Abstract: Forty percent of edible produce is wasted because of consumers' aversion toward esthetical imperfections related to size, shape, and blemish for produce. This phenomenon has huge implications in terms of both environmental sustainability and food security, and calls for the development of interventions that could facilitate the sale of products which would otherwise go to waste. This research provides an explanation for why transforming the physical state of imperfect produce—that is, by physically processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…This approach is viable, assuming the imperfectness does not impact flavor or texture. This finding is consistent with those of Barone et al . (2021), such that the transformation of the physical appearance of imperfect produce could improve consumer acceptance.…”
Section: Discussionsupporting
confidence: 94%
“…This approach is viable, assuming the imperfectness does not impact flavor or texture. This finding is consistent with those of Barone et al . (2021), such that the transformation of the physical appearance of imperfect produce could improve consumer acceptance.…”
Section: Discussionsupporting
confidence: 94%
“…At the same time, however, negative perceptions can arise from the abnormal appearance of suboptimal food. For example, externally deviated fruits and vegetables are often seen by consumers as not being prototypical (Hingston and Noseworthy, 2020;Barone et al, 2021) and thus as less nutritious, fresh, attractive and tasty than optimal looking products, sometimes even being viewed with disgust and regarded as risky to consume (Jaeger et al, 2018;Loebnitz and Grunert, 2018;Cooremans and Geuens, 2019;Schifferstein et al, 2019;Hingston and Noseworthy, 2020;Pfeiffer et al, 2021).…”
Section: Ambivalence Towards Suboptimal Foodmentioning
confidence: 99%
“…Prolific is a professional online survey platform with more than 1.3 million users from different backgrounds. Prolific has been widely used in consumer behavior research and has shown good reliability (e.g., Barone et al, 2021; Li & Shin, 2022; Wang, Raghunathan, & Gauri, 2022). A total of 100 participants (75 males) were recruited in the experiment for a cash payment (approximately £1).…”
Section: Study 2a: Disease Threat and Death‐related Thoughtsmentioning
confidence: 99%